Preventing occupational injury among police officers: does motivation matter? - Chan, Derwin; Webb, D.; Ryan, R.; Tang, T.; Yang, S.X.; Ntoumanis, Nikos; Hagger, Martin (Oxford University Press, 2017)
Background: Injury prevention is an important issue for police officers, but the effectiveness of prevention initiatives is dependent on officers' motivation toward, and adherence to, recommended health and safety guidelines. Aims: To understand effects of police officers' motivation to prevent occupational injury on beliefs about safety and adherence to injury prevention behaviours. Methods: Full-time police officers completed a survey comprising validated psychometric scales to assess autonomous, controlled and amotivated forms of motivation (Treatment Self-Regulation Questionnaire), behavioural adherence (Self-reported Treatment Adherence Scale) and beliefs (Safety Attitude Questionnaire) with respect to injury prevention behaviours. Results: There were 207 participants; response rate was 87%. Hierarchical multiple regression analyses demonstrated that autonomous motivation was positively related to behavioural adherence, commitment to safety and prioritizing injury prevention. Controlled motivation was a positive predictor of safety communication barriers. Amotivation was positively associated with fatalism regarding injury prevention, safety violation and worry. Conclusions: These findings are consistent with the tenets of self-determination theory in that autonomous motivation was a positive predictor of adaptive safety beliefs and adherence to injury prevention behaviours.